EDUCATIONAL SUPERVISION IN INCLUSIVE SCHOOL SETTINGS: SYSTEMATIC LITERATURE REVIEW - Saripudin Saripudin; Dodo Murtado; Maesaroh Lubis (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the patterns, characteristics, and effectiveness of educational supervision in inclusive school settings through a systematic literature review approach. The methodology used PRISMA 2020 with a literature search in five international databases for the period 2021-2025, resulting in 20 high-quality articles for analysis. The findings show the evolution of supervision models from a traditional hierarchical approach to a collaborative-transformational paradigm. Four effective supervision models were identified: transformational supervision, instructional leadership supervision, collaborative supervision, and distributed leadership model. The transformational supervision model showed significant changes in teachers' attitudes toward inclusive education, while instructional leadership had a 63.7% correlation with student academic achievement. Components of effective supervision include academic aspects through curriculum and IEP adaptation, professional aspects through teacher self-efficacy development, and organizational aspects through systematic management. Internal factors such as supervisor competence and an inclusive culture, as well as external factors such as policy support, determine successful implementation. Key challenges include issues of bullying, technological barriers, and the complexity of AI integration in supervision. The study recommends developing a contextual supervision model for Indonesia, taking into account local cultural characteristics and resource availability.